Multivariate analyses of the physicochemical properties of turnip (Brassica rapa L.) chips dried using different methods. Issue 4 (11th March 2020) - Xue, You-Lin; Chen, Jia-Nan; Han, Hao-Ting; Liu, Chun-Ju; Gao, Qi; Li, Jia-Heng; Li, Da-Jing; Tanokura, Masaru; Liu, Chun-Quan
Abstract: The turnip is a traditional "medicine food homology" vegetable in China, but the processing of it remains traditional and limited. To increase and diversify the consumption of turnips, freeze drying (FD), explosion puff drying (EPD), infrared drying (ID), and hot air drying (AD) were used to produce turnip chips. FD chips maintained most of the starch, total sugar, vitamin C, and volume ratio, followed by EPD chips, which exhibited better crisp values and rehydration rate. These results suggest EPD as a favorable method for turnip chip production. The physicochemical properties of turnip chips dried using different methods differed greatly from each other. Principal component analysis revealed that FD produced the best chips, followed by EPD. Hierarchical cluster analysis and orthogonal projection on latent structure-discriminant analysis identified the volume ratio as the characteristic property of FD chips and the contents of soluble dietary fiber and insoluble dietary fiber as the characteristic properties of ID chips, which indicated that multivariate analyses may be used to classify dried products and identify their characteristic properties.